2011
DOI: 10.1093/nar/gkr1281
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human polynucleotide phosphorylase: insights into its domain function in RNA binding and degradation

Abstract: Human polynucleotide phosphorylase (hPNPase) is a 3′-to-5′ exoribonuclease that degrades specific mRNA and miRNA, and imports RNA into mitochondria, and thus regulates diverse physiological processes, including cellular senescence and homeostasis. However, the RNA-processing mechanism by hPNPase, particularly how RNA is bound via its various domains, remains obscure. Here, we report the crystal structure of an S1 domain-truncated hPNPase at a resolution of 2.1 Å. The trimeric hPNPase has a hexameric ring-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 51 publications
4
87
1
Order By: Relevance
“…(III) En route, the RNA strand makes nonequivalent contacts with the KH domains (16), in addition to making contact within a putative core binding site (red asterisks). long 3= overhang to thread an RNA into the cleavage channel of human PNPase is also consistent with the simultaneous engagement of RNA 3= termini by both S1 and KH domains and the "hands on a rope" model (45). We predict that KH domains with enhanced affinity for RNA may prove inhibitory to PNPase by trapping RNA on the surface and inhibiting ratcheting.…”
Section: Figsupporting
confidence: 74%
See 1 more Smart Citation
“…(III) En route, the RNA strand makes nonequivalent contacts with the KH domains (16), in addition to making contact within a putative core binding site (red asterisks). long 3= overhang to thread an RNA into the cleavage channel of human PNPase is also consistent with the simultaneous engagement of RNA 3= termini by both S1 and KH domains and the "hands on a rope" model (45). We predict that KH domains with enhanced affinity for RNA may prove inhibitory to PNPase by trapping RNA on the surface and inhibiting ratcheting.…”
Section: Figsupporting
confidence: 74%
“…From recent structural determinations of PNPase and its homologues, it appears that the KH and S1 domains communicate with the conformationally dynamic catalytic core (15,19,45). Accordingly, an additional role for the KH domain may be the modulation of the size of the narrow "gateway" aperture to regulate substrate accommodation within the channel upon RNA binding.…”
Section: Figmentioning
confidence: 99%
“…Utilizing PNPase for RNA import into the mitochondrion requires the presence of a specific stem-loop secondary structure in the target RNA [57,92]. Interestingly, Barrey et al found that pre-miRNA-302a and pre-let-7b are predicted to fold into these stem-loop configurations, leading to the assumption that PNPase could be critical for the import of these pre-miRNAs into the mitochondrion [5].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a major determining factor between RNA degradation or transport by PNPase seems to be the length of the RNA species’ 3′ overhang. Wang et al showed that an 8 nucleotide (nt) 3′ overhang of a mRNA species resulted in degradation while a 0–2 nt 3′ overhang led to transport [57,84]. Other studies suggest that the machinery facilitating protein import into the mitochondria may also contribute to RNA import [3,36,54,75,78,81,82].…”
Section: Introductionmentioning
confidence: 99%
“…Single-stranded miRNA can be degraded by the 5 0 -3 0 exoribonuclease XRN2 or 3 0 -5 0 exoribonuclease human polynucleotide phosphorylase [50,51]. Previous studies have shown that the binding of pre-miRNAs to protein components such as MCPIP1 can facilitate the process of pre-miRNA degradation [52].…”
Section: Dna Damage Modulates Mirna Degradationmentioning
confidence: 99%